Development and application of targeted multiplex polymerase chain reaction to help diagnose infectious uveitis: Oral Presentation - Observational Study - General practitioner - Rachel Ethelind (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Clinical pattern recognition is paramount in uveitis diagnosis. Pathogen detection from ocular fluid samples is often necessary to support infectious uveitis diagnosis, particularly in cases presenting with atypical clinical appearance. This study aims to present the process of developing targeted multiplex PCR and its application in infectious uveitis. Methods : This was a cross sectional study to evaluate the diagnostic performance of targeted multiplex PCR in infectious uveitis. We obtained ocular fluid samples and reviewed medical records of uveitis patients who underwent ocular fluid analysis at Cipto Mangunkusumo Hospital from February 2022 to March 2023. PCR detection threshold values (DNA copies/mL) were 10.9 for Mycobacterium tuberculosis (Mtb), 672 for Epstein-Barr virus, 4.77 for Cytomegalovirus, 6.37 for Toxoplasma gondii, and 5.53 for Herpes simplex virus. With every two-fold increase of pathogen selection, this method requires a half volume of extracted DNA template from aqueous/vitreous samples than uniplex PCR. The ophthalmologist selected the pathogen combination to be detected, allowing for a tailored examination. Results : Forty-seven aqueous or vitreous samples were analyzed. The positivity rate was 23.4% (11/47) with Mtb yielded the highest positivity (7/34; 20.6%). With final diagnosis as a reference, targeted multiplex PCR resulted in 32.3% sensitivity, 93.8% specificity, 90.9% positive predictive value and 19.2% negative predictive value. Conclusion : With its high specificity, targeted multiplex PCR is useful as a confirmatory but not screening tool in uveitis diagnosis. Ocular fluid analysis is an important part of stepwise diagnostic approach in uveitis.